(untitled) (Acta Scientiarum. Biological Sciences, 2021)
The aim of this work was to evaluate the growth and the proximate composition of the mycelium-based bocaiuva pulp with the edible mushroom Pleurotus ostreatus on green bocaiuva flour added with different sources of nitrogen (urea, ammonium nitrate and sulfate ammonia). Growth was monitored by kinectics. At the end, the proximate composition of the best three treatments (dehydrated green bocaiuva pulp and water, T1; dehydrated green bocaiuva pulp and ammonium nitrate, T3; and green bocaiuva pulp/wheat bran and ammonium nitrate, T7) was determined. Ammonium nitrate was the nitrogen source that showed the greatest growth in both substrates (T3:8.33 cm and T7:7.67 cm) in relation to the other treatments (4.67 to 7.17 cm), with emphasis on the green bocaiuva pulp. The substrate with green bocaiuva pulp and water was the one that showed the highest growth (7.50 cm), which was close to the treatment with mixed substrate and ammonium nitrate (7.67 cm). The treatment with the green bocaiuva pulp and ammonium nitrate (T3) was highlighted due to its significant increase in proteins (9.42 g 100 g-1) and fibers (5.21 g 100 g-1), and decrease in carbohydrates (9.52 g 100 g-1), in comparison to the other treatments T7 (8.94, 2.16, and 5.99 g 100 g-1, respectively) and T1 (2.78, 4.33, and 2.28 g 100 g-1, respectively). The product obtained from the growth of P. ostreatus in green bocaiuva pulp presents promising perspectives to be utilized as raw material for the development of new food products with added nutritional value.